Stability of Hydrocortisone in Oral Powder Form Compounded for Pediatric Patients in Japan - Jumpei Saito; Nozomi Yoshikawa; Takehisa Hanawa; Ayuna Ozawa; Takahiro Matsumoto; Tsutomu Harada; Kana Iwahashi; Hidefumi Nakamura; Akimasa Yamatani (MDPI AG, 2021)
Hydrocortisone has been utilized in the management of adrenal insufficiency. For pediatric patients, the commercially available enteral form of hydrocortisone tablets (Cortoril®) is administered in powder form after being compounded by a pharmacist. However, the stability and quality of compounded hydrocortisone powder have not been verified. In this study, we formulated a 20 mg/g oral hydrocortisone powder by adding lactose monohydrate to crushed and filtered hydrocortisone tablets and assessed the stability and physical properties of this compounded product in polycarbonate amber bottles or coated paper packages laminated with cellophane and polyethylene. Stability was examined over 120 days in three storage conditions: closed bottle, in-use bottle, and laminated paper. Drug dissolution and powder X-ray diffraction analysis were conducted to assess its physicochemical stabilities. Validated liquid chromatography-diode array detection was used to detect and quantify hydrocortisone and its degradation products. Although impurity B (cortisone) and G (hydrocortisone-21-aldehyde) were found after 120 days of storage, no crystallographic and dissolution changes were noted. Hydrocortisone content was maintained between 90% and 110% of initial contents for 120 days at 25 ± 2 °C and 60 ± 5% relative humidity in all packaging conditions.